Un’identità porosa: l’intersezione linguistica e culturale nella scrittura di Marica Bodrožić - Rocco Guaragnone (Dive-In)
The article offers an analysis about the interconnection between migrants and host culture through the work Sterne erben, Sterne färben. Meine Ankunft in Wörtern by the writer of Croatian origins Marica Bodrožić. The definition of zweite Muttersprache, regarding German language, shows an inclusion process necessarily related to identity and language. Her writing, characterized by her cultural identities, becomes an example of that plurality dominating the East-West relationship in which the contrast has been replaced by hybridization. By adopting a horizontal perspective, heterogeneities coexist without hierarchies and prerogatives of assimilation. Accordingly, a porose identity finds a place in an in-between space of cultural comparison, expressed by the Dazwischen concept. Indeed, the claim of national belonging is replaced by an in-betweenness condition lived by migrant, the ‘Other’ in a transience beyond nationalistic borders. This condition is a proof that the host culture belongs to migrants, to Others as well.